2014
DOI: 10.1093/geront/gnu073
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Religiosity on Depression: A 2-Year Prospective Study

Abstract: Findings suggest that both organizational and nonorganizational forms of religiosity affect depression outcomes in different circumstances (i.e., onset and recovery, respectively). Important strategies to prevent and relieve depression among older adults may include improving access and transportation to places of worship among those interested in attending services and facilitating discussions about religious activities and beliefs with clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 46 publications
4
59
1
5
Order By: Relevance
“…17 Ronneberg found protective effects of religiosity on depression in older adults of Massachusetts Boston. 5 At 45% and 37%, respectively, high frequency of religious service attendance was more likely to be reported by non-depressed than depressed respondents, whereas depressed respondents were more likely to report low or no service attendance than their non-depressed counterparts.…”
Section: Discussionmentioning
confidence: 89%
“…17 Ronneberg found protective effects of religiosity on depression in older adults of Massachusetts Boston. 5 At 45% and 37%, respectively, high frequency of religious service attendance was more likely to be reported by non-depressed than depressed respondents, whereas depressed respondents were more likely to report low or no service attendance than their non-depressed counterparts.…”
Section: Discussionmentioning
confidence: 89%
“…The association between religiousness and depressive symptoms has been investigated in different populations, and in most of them, the most intense religiousness is associated with lower frequency of depressive symptoms 2,4,7,9,23,24 decrease of the symptoms 25 or remission 1,26 . So far, only one epidemiological population-based study has tested hypotheses of the association between religiousness and the use of antidepressants, and it was done among adults 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This idea is reinforced by the fact that this association has been observed among elderly people with depressive symptoms, unlike that which occurred among those without them, in which the association was not significant (results not shown). In Bambuí, a recent ethnographic study showed that, for the elderly, religious coping is important in confronting disability, leading to the acceptance of this condition as something inherent to the aging process and allowing for less distress when living with the condition, to estab- 4 , since attendance at religious services promotes social interaction, decreasing isolation and loneliness, that are consequence or strengthen depressive symptoms 1,4,28 . On the other hand, social support has been associated with the use of antidepressants 14 and adherence to drug treatment of depression 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also stated that there is a wide spectrum of psychosocial factors that can empower older adults against stressful life events and prevent depression (15). Social network support and spirituality are two of the most effective modifiers that are worth mentioning (13,16). International reports present a wider range of protective factors.…”
Section: Contextmentioning
confidence: 99%